2016
DOI: 10.1186/s13019-016-0442-y
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review on learning curve associated problems in endoscopic vein harvesting and the requirement for a standardised training programme

Abstract: Endoscopic vein harvesting is becoming one of the most favourable vein harvesting techniques in multiple bypass coronary surgery, due to its short term post-operative benefits with high patient satisfaction. However, long-term graft patency has been both supported and questioned in the literature. Graft failure can be affected by harvesting methods and operator’s experience. Endoscopic vein harvesting is associated with a learning curve period, during which the incidence of vein trauma is high due to unfamilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 74 publications
0
27
0
Order By: Relevance
“…Repeat angina and reintervention in patients in this study were due mainly to grafting technique and technical error,27,28 poor target-artery quality,11 progression of native coronary artery diseases,8 and previous stent blockage after CABG. Although the importance of grafting technique is highlighted by our findings, we did not observe significant intraoperator effects on MACE outcomes.…”
Section: Discussionmentioning
confidence: 72%
“…Repeat angina and reintervention in patients in this study were due mainly to grafting technique and technical error,27,28 poor target-artery quality,11 progression of native coronary artery diseases,8 and previous stent blockage after CABG. Although the importance of grafting technique is highlighted by our findings, we did not observe significant intraoperator effects on MACE outcomes.…”
Section: Discussionmentioning
confidence: 72%
“…It is known that vein graft quality depends on technical experience of the harvester. 6,12 The whole training process could be time consuming but is an essential element of obtaining a good quality vein conduit for better clinical outcomes. 6 Obviously, input costs of EVH compared with SVH are higher, but the final cost-benefit calculation presented recoverability of costs, so that EVH is a cost-effective alternative to SVH.…”
Section: Discussionmentioning
confidence: 99%
“…6,12 The whole training process could be time consuming but is an essential element of obtaining a good quality vein conduit for better clinical outcomes. 6 Obviously, input costs of EVH compared with SVH are higher, but the final cost-benefit calculation presented recoverability of costs, so that EVH is a cost-effective alternative to SVH. 3,13,14 Endothelial function is a determinant of long-term graft patency and late vein graft failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ERAH was also found to take a longer duration as compared to ORAH with an associated steep learning curve in inexperienced hands [36] . The reported learning curve for endoscopic harvest ranges from 5 to 30 cases [37] . Although, Kiaii et al [38] found that the endoscopic approach requires a significantly lower harvest time (36.5 ± 9.4 min) compared to the open approach (57.7 ± 9.4 min) when performed by a surgeon adequately experienced in endoscopic harvest.…”
Section: Radial Artery Graft Harvest Could Be Performed Open or Endosmentioning
confidence: 99%